Design of Mercury Interim Storage for Medical Devices Containing Mercury - Putri Natari Ratna; Sri Lusiani; Noor, M. R.; R. N. Pratama; R. B. Nareswari; S. Zikri (JST (Jurnal Sains dan Teknologi), 2023)
The Indonesian government is committed to protecting the public from the dangers of mercury. One of the attempts planned is to withdraw mercury medical devices from all health facilities. Storage and monitoring of these medical devices must also be carried out properly and follow mercury handling procedures through mercury interim storage facilities. In building Mercury Interim Storage (MIS), several things need to be designed, including storage areas, ventilation systems, office areas, leak containers, and storage shelves. All of these designs must meet the guidelines and criteria to store mercury safely before being stored in a final storage. In this study, Mercury Interim Storage is designed to keep thermometers and sphygmomanometers, which is estimated to accommodate 10,000 and 1,900 units, respectively.